Nonlinear Dimensionality Reduction of Spectrograms (2009)
Embodiments of the invention disclose a system and a method for reducing a dimensionality of a spectrogram matrix. The method constructs an intermediate time basis matrix and an intermediate frequency basis matrix and applies iteratively a non-negative matrix factorization (NMF) to the intermediate time basis matrix and the intermediate frequency basis matrix until a termination condition is reached, wherein the NMF is subject to a constraint on a an independence regularization term, wherein the constraint is in a form of a gradient of the term.